Fitness Estimation for Ecological Studies: An Evaluation in Columbian Ground Squirrels - Dobson, F. Stephen; Murie, Jan O.; Viblanc, Vincent A. (Frontiers in Ecology and Evolution, 2020)
The topics of evolution by natural selection and ecological interactions are closely intertwined. Thus, measurements of evolutionary fitness are ubiquitous in the ecological literature. As an empirical problem, the components of fitness, reproduction and survival, may be analyzed to produce fitness estimates in several ways. These can be divided into annual estimates that are most appropriate for short-term (e.g., annual) and experimental studies, and lifetime fitness estimates that are most appropriate for evaluating functional organismal traits. The latter are appropriate for comparative studies¬¬ of natural selection in species with lifetimes that extend over several years. These estimates may also be particularly useful for estimating the direct and indirect components of inclusive fitness, an important topic for the evolution of cooperation. We present examples of some of these alternatives from our research on Columbian ground squirrels (Urocitellus columbianus). Using empirical data, we also test the degree of correspondence of annual fitness, lifetime reproductive success, and individual fitness measures that are based on matrix methods.